Mucuripe:verticalização, mutações e resistências no espaço habitado - Ramos, Lidiane da Costa (2003)
Mucuripe, one of the most ancient boroughs of Fortaleza is undergoing a process of urban reform in which the poor part of the population is being excluded. This borough is famous for its strong fishing tradition and it is loosing its characteristic as time goes by, due to the great property speculation in this area of the city, in which we can see that when they relocate people from their social area they fragment the social relationships, thus risking the identity of the place. In removing the poor people, as well as the fishermen, who are part of the ancient process of Mucuripe, provokes conflicts and resistance of the people. But with the verticalization, which is a product of property speculation in this borough, the conflict became more intense and the main goal of the study is to understand the process of production and appropriation of Mucuripe before the crescent verticalization of this area. And to understand this process it was necessary the seach of a theoretical-countersign concept able to provide a approach intersubjective. It was also worth the analyses of the cartographic material which information about the income of each property, as well as the population density and the numbers of apartment in the borough and the identification of the Mucuripe´s buildings, which the purpose of demonstrating a space concentration of this verticalization. The cartographyc material, on the other hand provides a notion of time, by showing the transformation in this space at the level of lansdcape. The verticalization of Mucuripe reveals a strong socialspecial segregation and it has contributed to aggravation of the problem of the environmental situation of this borough, The Caravelle building, which was built on the edge of the Teixeira´s hill, while the population of the Maceió´s brook demonstrated the terrible conditions of life of the population that lived in risky areas in Mucuripe demonstrating the enviromental degradation in this borough. We see verticalization in Mucuripe as part of a global process of production in the cities of a modern project, in which as turning into a more “modern city”, it also becomes more excluding.